Between State and Nation : Diaspora Politics and Kin-state Nationalism in Hungary. - Waterbury, Myra A. (Palgrave Macmillan, 2010)
Why and how do states in Eastern Europe take action on behalf of ethnic kin in neighboring states? Based on a qualitative study of Hungary and its changing relationship to the three million ethnic Hungarians in neighboring states, the book argues that it is not the ties of ethnicity, but the political interests of kin-state elites that drive engagement with co-ethnics beyond the border. The resulting policies are then shaped and constrained by the process of European Union integration and by contestation over the boundaries of identity and citizenship.